Study of Lectin-like Protein from Terminalia catappa (TC) Seeds for Its Physicochemical and Antimicrobial Properties - Fakeha Mohammed Rehan Shaikh; Ashish Sambhaji Uzgare (Chemistry Proceedings)
Lectins are a diverse group of proteins crucial in numerous biological activities. They exist in plants, animals, and microorganisms, each with unique structural and functional characteristics. Their ability to exhibit hemagglutination and specifically bind with carbohydrates allows lectins to participate in processes like cell adhesion, immune responses, and intracellular signaling pathways. Lectins are particularly noted for their roles in counteracting viral diseases, regulating blood sugar levels, fending off pathogens, and preventing cancer progression. These natural compounds offer potential therapeutic benefits in various healthcare applications. Terminalia catappa (TC), known as Indian almond, is a large tropical tree containing flavonoids, tannins, saponins, and phytosterols with medicinal values. This research aimed to investigate the partial purification and characterization of lectins from TC seeds. The process involved extracting and partially purifying the lectin, testing it for hemagglutination assay, temperature and pH stability, EDTA dependence, effect of metal ions, specific sugar determination, and antibacterial activity. Hemagglutination activity was observed in human blood group B+. The findings suggest TC seed lectin is remarkably stable within a moderate temperature range and across a broad pH spectrum. The dependence on EDTA for hemagglutination activity indicates a potential metalloprotein nature, with notable interactions with various metal ions, except Hg2⁺. While the initial antimicrobial assessment against common bacteria yielded limited results, further studies hold promise for uncovering the full potential of TC seed lectin in healthcare and therapeutic advancements.